2019
DOI: 10.1016/j.prro.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Robustness Analysis for External Beam Radiation Therapy Treatment Plans: Describing Uncertainty Scenarios and Reporting Their Dosimetric Consequences

Abstract: Purpose: With external beam radiation therapy, uncertainties in treatment planning and delivery can result in an undesirable dose distribution delivered to the patient that can compromise the benefit of treatment. Techniques including geometric margins and probabilistic optimization have been used effectively to mitigate the effects of uncertainties. However, their broad application is inconsistent and can compromise the conclusions derived from cross-technique and cross-modality comparisons. Methods and Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 57 publications
(74 reference statements)
1
58
0
Order By: Relevance
“…The value of 3 mm was the margin of uncertainty for patients with head and neck tumors, allowing for machine variability. The value of 3.5% was the range of uncertainty resulting from uncertainties in the range calculation, the acquisition of CT number, and the CT number-stopping power conversion table [13, 16].…”
Section: Methodsmentioning
confidence: 99%
“…The value of 3 mm was the margin of uncertainty for patients with head and neck tumors, allowing for machine variability. The value of 3.5% was the range of uncertainty resulting from uncertainties in the range calculation, the acquisition of CT number, and the CT number-stopping power conversion table [13, 16].…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5] When the dosimetric objective is mean dose or a relative dose-volume metric, the variation in contouring can introduce significant uncertainty. As described in Yock et al, 1 the dosimetric impact has been demonstrated to be as much as 5% for clinically relevant uncertainties. In our institution's contour review, we observed a mean heart volume of 600 cc with a standard deviation of 300 cc My point is that if we as clinical physicists do not explore such sources of uncertainty and clearly explain them to our physician colleagues, we are doing our physician colleagues (and by extension their patients) a disservice by not understanding how these factors interrelate to impact the patient's care.…”
mentioning
confidence: 77%
“…When the dosimetric objective is mean dose or a relative dose–volume metric, the variation in contouring can introduce significant uncertainty. As described in Yock et al, 1 the dosimetric impact has been demonstrated to be as much as 5% for clinically relevant uncertainties. In our institution's contour review, we observed a mean heart volume of 600 cc with a standard deviation of 300 cc due to differences among planners in the extent of superior pericardium contoured — yet the main dosimetric objective for non‐SBRT plans is mean dose.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The 'robustness' of proton plans to physical and biological uncertainties is a topic receiving substantial attention, as summarized in recent reviews [11,12]. Within commercial proton treatment planning systems (TPSs), physical uncertainties (both geometrical isocenter shifts and uncertainties in Hounsfield Unit (HU) to proton stopping power ratio (SPR) conversion) can not only be analyzed (in terms of dosimetric effect) but also used to drive plan treatment optimizations [12].…”
Section: Introductionmentioning
confidence: 99%